(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
If in the case of consumer law, as protected persons are the consumers, then in the case of competition law, the protected entities are the competitors. A combination of actions in competition law presupposes that the same commercial offer satisfies several individual interests of consumers. In the strictest sense, such a combination implies the same legal fact, simultaneously opening up more possibilities for the consumer to choose due to loyal offers from a professional, if he is monopolistic or dominant in the market. More broadly, it can also be accepted that offers can be combined from several competing professionals relating to the same product or service and concerning the same individual interest of a consumer. The possible complementary effects of common law, which would justify the non-limitation of a specific piece of legislation, can never lead to a new monopoly. In some cases this will make competition law more effective and, in other cases, provide marginal and non-exclusive protection to consumers who do not have a direct right guaranteed by competition law. The purpose of this article is to demonstrate the interdependent relationship between competition law and consumer law, from the perspective that both have the same common goal, namely to limit abuses by professionals in their economic activity, especially during pandemic times.